Sustainable Development, Climate Politics and EU Leadership: Who Else Can Lead the World? - Clémençon, Raymond (European Journal of Sustainable Development, 2016)
Abstract: The pressure on EU countries to abandon a leadership role on sustainable development and climate change politics is growing. However, no other source of global leadership is emerging that could fill the gap. The present analysis examines the relative role of four political drivers that influence policy and governance responsesto global environmental issues.The conclusion is that over the last two decades,international negotiations, civil society activism, and private sector initiatives on their own have not been decisive factorsshaping outcomes whilepolitical opportunity structures in key countries explain broad policy trajectories that favor or undermine sustainable development policies. EU countries - where Green Parties at times have been able to critically shape policy direction - are the only actors that have developed the socio-political and economic foundation for a coherent approach to sustainable development. Such a foundation on the other hand is missing in the United States and in key emerging economies. Key words: Sustainable development, climate change, global environmentalism, EU leadership, U.S. climate politics